2012
DOI: 10.1016/j.eeh.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Between conquest and independence: Real wages and demographic change in Spanish America, 1530–1820

Abstract: On the basis of a newly constructed dataset, this paper presents long-term series of the price levels, nominal wages, and real wages in Spanish Latin America -more specifically in Mexico, Peru, Bolivia, Colombia, Chile, and Argentina -between ca. 1530 and ca. 1820. It synthesizes the work of scholars who have collected and published data on individual cities and periods, and presents comparable indices of real wages and prices in the colonial period that give a reasonable guide to trends in the long run. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
2
17

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 26 publications
6
67
2
17
Order By: Relevance
“…REAL WAGES OF LABOURERS USING THE RESPECTABLE CONSUMER PRICE INDEX (CPI; Welfare ratio) Sources: See Appendix.AMÍLCAR E. CHALLÚ/AURORA GÓMEZ-GALVARRIATO they differ, expectedly, in their levels and volatility and the trend of «respectable» welfare ratio is even flatter.Our barebones price and real wage indexes are highly correlated with those ofAllen et al (2012) andArroyo Abad et al (2012), resulting in the similar trends shown inFigure 3. Yet the levels and the magnitude of changes were different.…”
supporting
confidence: 67%
“…REAL WAGES OF LABOURERS USING THE RESPECTABLE CONSUMER PRICE INDEX (CPI; Welfare ratio) Sources: See Appendix.AMÍLCAR E. CHALLÚ/AURORA GÓMEZ-GALVARRIATO they differ, expectedly, in their levels and volatility and the trend of «respectable» welfare ratio is even flatter.Our barebones price and real wage indexes are highly correlated with those ofAllen et al (2012) andArroyo Abad et al (2012), resulting in the similar trends shown inFigure 3. Yet the levels and the magnitude of changes were different.…”
supporting
confidence: 67%
“…Very long series of prices of all items in the basket (soap, candles, fuel, etc. For instance, in Arroyo-Abad et al (2012), the series of wages for Argentina between 1775 and 1810 results from combining data on «construction workers» (1775-1810) with «government officials» and «bricklayers» (1810-1860) from Buenos Aires; that for Peru mixes the wages of «mita workers» in Huamanga (1597-1603)a mining area in the Andeswith those of «porters» in Lima (1625-1760). Especialmente en el caso de las mujeres, y, en consecuencia, las rentas salariales de las familias tuvieron, en el largo plazo, una evolución bastante menos negativa que la de los jornales» (Llopis and García-Montero 2011, p. 296).…”
Section: Pre-independence Spanish Americansunclassified
“…Utilizando los datos ya disponibles para el Perú del siglo XIX y complementándolos con mi propio trabajo de archivo, este trabajo utiliza la metodología diseñada por Allen (2001) y ampliada por Arroyo Abad et al (2012). Como se detalla a continuación, la metodología también incluye otras canastas de consumo disponibles de otras fuentes.…”
Section: Salario Mínimo Vital Y Bienestarunclassified